Influence of Being Embodied in an Obese Virtual Body on Shopping Behavior and Products Perception in VR - Verhulst, Adrien; Normand, Jean-Marie; Lombart, Cindy; Sugimoto, Maki; Moreau, Guillaume (Frontiers in Robotics and AI, 2018)
Research in \ac{VR} showed that embodiment can influence participants' perceptions and behavior when embodied in a different yet plausible virtual body. In this paper, we study the changes an obese virtual body has on products perception (\eg taste, etc.) and purchase behavior (\eg number purchased) in an immersive virtual retail store. Participants (of a normal BMI on average) were embodied in a normal (N) or an obese (OB) virtual body and were asked to buy and evaluate food products in the immersive virtual store. Based on stereotypes that are classically associated with obese people, we expected that the group embodied in obese avatars would show a more unhealthy diet, (\ie buy more food products and also buy more products with high energy intake, or saturated fat) and would rate unhealthy food as being tastier and healthier than participants embodied in ``normal weight'' avatars. Our participants also rated the perception of their virtual body: the OB group perceived their virtual body as significantly heavier and older. They also rated their sense of embodiment and presence within the immersive virtual store. These measures did not show any significant difference between groups. Finally, we asked them to rate different food products in terms of tastiness, healthiness, sustainability and price. The only difference we noticed is that participants embodied in an obese avatar (OB group) rated the coke as being significantly tastier and the apple as being significantly healthier. Nevertheless, while we hypothesized that participants embodied in a virtual body with obesity would show differences in their shopping patterns (\eg more ``unhealthy'' products bought) there were no significant differences between the groups. We discuss these results and propose that, unlike previous research, our participants were embodied in virtual avatars which differed greatly from their real bodies. Indeed, obese avatars should modify users motion and not only their visual characteristics (e.g. hair or skin color, etc.). Unfortunately, we did not manipulate participants' motion to increase their feeling of being obese. This main difference could then explain why we did not notice any important modification on participants' behavior and perceptions of food products.